2019
DOI: 10.1177/0300060519879588
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR and RFC1 gene polymorphisms with methotrexate efficacy and toxicity in Chinese Han patients with rheumatoid arthritis

Abstract: Objective The objective was to explore the association of methylene tetrahydrofolate reductase ( MTHFR) C667T and A1298C and reduced folate carrier 1 ( RFC-1) A80G single nucleotide polymorphisms (SNP) with rheumatoid arthritis (RA) and efficacy and toxicity of methotrexate (MTX) treatment in Chinese Han patients in Henan, China. Methods Two hundred ninety-six patients with RA were enrolled (cases) and 120 healthy individuals served as controls. The genotypes of MTHFR C667T and A1298C SNP and RFC-1 A80G SNP we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…According to several studies, the MTHFR variants A1298C and C677T are two of the most important polymorphisms associated with MTX toxicity [ 16 , 19 , 20 , 21 ]. The MTHFR A1298C polymorphism has been reported to lead to a 60% reduction in enzymatic activity in patients homozygous for 1298C, causing MTX intolerance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies, the MTHFR variants A1298C and C677T are two of the most important polymorphisms associated with MTX toxicity [ 16 , 19 , 20 , 21 ]. The MTHFR A1298C polymorphism has been reported to lead to a 60% reduction in enzymatic activity in patients homozygous for 1298C, causing MTX intolerance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of study selection is shown in Figure 1 , with the details of the inclusion and exclusion of studies illustrated. For pooling MAF, a total of 264 studies were identified from databases, among which 30 case-control studies were included for pooling minor allele prevalence ( 19 48 ), which all reported the MAF in non-ASD populations in Chinese Han. For the targeted gene effect, we yielded 119 papers initially and finally, six publications ( 49 – 54 ) were included in the present meta-analysis, with a total of 2,258 cases and 2,073 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis revealed that the exclusion of Wang et al 19 and Yamamoto et al 20 studies resulted in a borderline protective role of RFC1 A-allele against MTX toxicity 19,20 (Figure 4). Exclusion of other studies showed no difference in the association.…”
Section: Resultsmentioning
confidence: 99%
“…32 Robustness of meta-analysis was ensured by the sensitivity analysis. The exclusion of Wang et al 19 and Yamamoto et al 20 studies resulted in a borderline protective role of the RFC1 A-allele against MTX toxicity.…”
Section: Discussionmentioning
confidence: 99%